Novel automated immune turbidimetric assay for routine urinary cystatin-C determinations. (16th February 2018) - Szirmay, Balázs; Kustán, Péter; Horváth-Szalai, Zoltán; Ludány, Andrea; Lakatos, Ágnes; Mühl, Diána; Wittmann, István; Miseta, Attila; Kovács, Gábor L.; Kőszegi, Tamás
Aim: There is no commercially available urinary cystatin-C (u-CYSC) test in the market. Therefore, we optimized and validated an automated immune turbidimetric test for u-CYSC measurements and investigated u-CYSC concentrations in acute and chronic diseases which might lead to renal tubular disorders.Materials & methods: A particle-enhanced immune turbidimetric assay was adapted and validated on a Cobas 8000/c502 analyzer. Urine samples of different patient groups were also analyzed.Results: Our method showed excellent analytical performance. U-CYSC/u-creatinine (u-CREAT) was higher in sepsis-related acute kidney injury group (p < 0.001) compared with controls and to patients with chronic hypertension and Type 2 diabetes.Conclusion: We validated a fast, sensitive, fully automated u-CYSC assay which is ideal for routine use and might be a potential complementary laboratory test to evaluate renal tubular function.